Decontamination of Listeria monocytogenes in enoki mushrooms using a 405-nm light-emitting diode illumination combined with organic acid dipping. (November 2020) - Yoon, Jae-Hyun; Chu, Hyeonjin; Jeong, Do-Young; Choi, Songyi; Hwang, In-Jun; Lee, Sun-Young; Kim, Se-Ri
Abstract: This study was undertaken to examine the effect of a 405-nm light-emitting diode (LED) illumination alone or combined with 3% organic acid dipping on the survival of Listeria monocytogenes in enoki mushrooms stored at 5 °C. Less than 1.0 or 2.1–4.4 log-reductions were achieved when L. monocytogenes in enoki mushrooms was illuminated with a 405-nm LED at 5 °C for 3 h or immersed in 3% malic acid (MA) or lactic acid (LA) at 25 °C for 30 min. Particularly, L. monocytogenes in mushrooms was significantly ( p  < 0.05) reduced by ≥ 4.6 log CFU g −1 after a 405-nm LED illumination (3 h) at 5 °C, followed by 3% LA dipping (30 min) at 25 °C, leading to its inability to recover in samples stored at 5 °C for up to 5 d. The combined action of a 405-nm LED and 3% LA altered the intracellular structure of L. monocytogenes cells, resulting in condensed granules or cytoplasmic protein agglutination. These findings indicate that the effectiveness of a 405-nm LED illumination can be higher when combined with organic acid dipping than that alone for decontaminating L. monocytogenes in enoki mushrooms without quality deterioration. Highlights: A 405-nm LED illumination (3 h) reduced L. monocytogenes in enoki mushrooms by < 1.0 log CFU g −1 . Soaking L. monocytogenes in mushrooms with 3% organic acids resulted in ≥4.4 log-reductions. L. monocytogenes was completely inactivated by LED illumination combined with MA dipping. No recovery of L. monocytogenes was observed in mushrooms after the sequential treatment. The sequential treatment caused a serious loss of cell membrane structure and integrity.